Avaliação dos impactos ambientais causados pela atividade de extração mineral classe II, para emprego imediato na construção civil. Estudo de caso da extração de areia em cavas submersa no município de Redenção – PA - SOUSA, Welison Teodoro de (2019)
Mining is an activity that generates environmental change, affecting not only the local landscape, but the ecosystem in general. The extraction of sand in submerged cava in the municipality of Redenção generates environmental impacts in the physical, biotic and anthropic environments, being these positive or negative. The methodology adopted in this research consisted of quantitative and qualitative character, using direct and indirect inductive methods, where primary data and secondary data were obtained with the objective of evaluating the environmental impacts caused by the mineral extraction activity class II sand In submerged cava in the municipality of Redenção / PA, from 2013 to 2016 by the technique of Environmental Impact Assessment, such as overlay mapping, check list and interaction matrices. Through the analyzes carried out, it is possible to verify the extensive areas that were explored without due license registry with the DNPM, allowing environmental impacts in the study area. The aggravating factors of the environmental impacts were evidenced by the AIA techniques in the years of 2013 to 2015, and with the technique of overlay mapping it was possible to quantify the amount of area explored illegally. The intensification of environmental control in a joint way is of paramount importance in order to reduce irregular practices, as well as require the assistance of a qualified technician for the projects, strengthening the environmental management system by forming multidisciplinary teams with the purpose of establishing a greater political and social commitment with the environment.